2021
DOI: 10.1186/s12014-021-09330-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics reveals the effect of Yigu decoction (YGD) on protein expression in bone tissue

Abstract: Background Osteoporosis (OP) is a systemic bone disease characterized by decreased bone mass, destruction of the bone tissue microstructure, increased bone brittleness and an increased risk of fracture. OP has a high incidence rate and long disease course and is associated with serious complications. Yigu decoction (YGD) is a compound prescription in traditional Chinese medicine that is used to treat OP. However, its mechanism in OP is not clear. This study used a tandem mass tag (TMT)quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…Reports on capsazepine suggest that it may direct bone marrow mesenchymal stem cells toward pro-osteogenic differentiation to combat OP, and the main mechanism may involve transient receptor potential cation channel subfamily V member 1 (TRPV1) intervention ( Pan et al., 2013 ; Xiao et al., 2019 ). There is no related research on how Phe-Tyr is involved in OP, but it has been reported in a recent study that Phe-Tyr affects the onset of diabetes as a substance affecting glucose metabolism ( Jahja et al., 2014 ; Strasser et al., 2015 ), which also confirms the finding in our previous study that there may be a relationship between senile OP and diabetes ( Zhang et al., 2021a ). Phe-Tyr is associated with inflammation of the bone and joint ( Muhammed et al., 2020 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Reports on capsazepine suggest that it may direct bone marrow mesenchymal stem cells toward pro-osteogenic differentiation to combat OP, and the main mechanism may involve transient receptor potential cation channel subfamily V member 1 (TRPV1) intervention ( Pan et al., 2013 ; Xiao et al., 2019 ). There is no related research on how Phe-Tyr is involved in OP, but it has been reported in a recent study that Phe-Tyr affects the onset of diabetes as a substance affecting glucose metabolism ( Jahja et al., 2014 ; Strasser et al., 2015 ), which also confirms the finding in our previous study that there may be a relationship between senile OP and diabetes ( Zhang et al., 2021a ). Phe-Tyr is associated with inflammation of the bone and joint ( Muhammed et al., 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the investigation of two groups of OP patients with different GM conditions due to intervention and the differences in the metabolites showed that the treatment group improved more than the control group. The BMD in the treatment group improved significantly more than that in the control group; the results also indicate that YGD not only improves BMD in OP patients but also improves the GM, which is indirectly involved in the prevention of OP, confirming the results of our previous study ( Li and Gong, 2021 ; Zhang et al., 2021a ). Among the top ten species, Escherichia-Shigella is mainly associated with the inflammatory response and lipid metabolism ( Cattaneo et al., 2017 ; Li et al., 2020 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Quantitative proteomic techniques have emerged as powerful tools for assessing dynamic changes in the bone proteome under physiological and pathological conditions. Stable isotope labeling-based methods such as tandem mass tag (TMT) [63,64] and isobaric tags for the relative and absolute quantitation (iTRAQ) [65] allow for the simultaneous quantification of thousands of proteins across multiple samples, enabling comprehensive analysis of bone proteome alterations [66][67][68]. Several quantitative proteomic studies have investigated changes in protein expression profiles during bone development, aging, and osteoporosis progression [18,59,69].…”
Section: Quantitative Proteomics In Assessing Dynamic Changes In Bone...mentioning
confidence: 99%
“…Postmenopausal osteoporosis is a systemic disease with a complex pathogenesis that affects bone metabolism. In recent years, proteomics has been increasingly applied to the study of bone physiology and pathology, especially PMOP (20)(21)(22). The main protein markers of osteoporosis gained from Several studies have demonstrated that exercise affects bone turnover and regulates bone formation through a variety of signaling pathways, such as receptor activator of nuclear factor kappa-Β ligand (RANKL)/RANK/osteoprotegerin pathway (30-32).…”
Section: Effect Of Moderate-intensity Treadmill Exercise On the Femor...mentioning
confidence: 99%